(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The results of research on optimization of sterilization conditions for some valuable medicinal plant species of the genus Ungernia Bunge (Amaryllidaceae J.St.-Hil.): U. sewertzowii (Regel) B. Fedtsch. and U. victoris Vved. ex Artjush., samples from the collection of the Botanical Garden named after F.N. Rusanov of the AScRUz – Corylus avellana L. (Betulaceae Gray) and Acer platanoides L. Crimson King (Acearceae Juss.) are presented in this article. It has been found that the most optimal sterilization protocol for explants of these species includes the use of the “Domestos” sterilizing agent, 70% ethanol and 4-6% sodium hypochlorite solution.